2012
DOI: 10.1007/s12402-012-0099-x
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ attitudes toward methylphenidate using n-of-1 trial: a pilot study

Abstract: To compare parents' attitudes toward methylphenidate treatment in children with attention deficit hyperactivity disorder employing two approaches: (1) a 2-week double-blind placebo-drug trial (n-of-1 trial), (2) a traditional prescription approach. The study group (N-50) and a comparison group (N-45) were recruited. The Abbreviated Acceptability Rating Profile was administered prior to and following the pediatricians' consultation, and in 2, 4, and 8 weeks after prescription. Complete data set was available fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…However, we are not aware of any bias related to the referral of children to our service or a bias related to randomization of ADHD subtypes in the placebo/drug trials. 45,54 Furthermore our results are valid for children with no associated disorders as formally diagnosed using the Diagnostic and Statistical Manual of Mental Disorders criteria. It is plausible that the exclusion of children with associated conduct and oppositional defiant disorders (ODD) has affected the proportion of children with hyperactive impulsive and combined ADHD in the present study.…”
Section: Limitationssupporting
confidence: 51%
See 1 more Smart Citation
“…However, we are not aware of any bias related to the referral of children to our service or a bias related to randomization of ADHD subtypes in the placebo/drug trials. 45,54 Furthermore our results are valid for children with no associated disorders as formally diagnosed using the Diagnostic and Statistical Manual of Mental Disorders criteria. It is plausible that the exclusion of children with associated conduct and oppositional defiant disorders (ODD) has affected the proportion of children with hyperactive impulsive and combined ADHD in the present study.…”
Section: Limitationssupporting
confidence: 51%
“…This approach was also found to be related to parents’ and children’s attitudes and maintenance on drug. 29,43 48 Mechanisms proposed to underlie the placebo effect include expectancy effect, conditioning, learning by imitation, and changes in the caregiver perception and action. 21,23 25 All these mechanisms are potentially responsible for the different response-related variables discussed below: Type of ADHD: The lack of difference in placebo response as related to the type of ADHD, the similar correlation of the response as related to baseline in the 2 subtypes and the significant relationship with clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Two trials, one of which was quasi-randomized, compared parents’ attitudes towards using methylphenidate in treating children with attention deficit hyperactivity disorder [ 10 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only one of the studies showed benefit of n-of-1 trials in the pre-specified primary outcome [ 17 ]. This trial, which was not truly randomized, showed higher acceptability of methylphenidate treatment among parents whose children underwent an n-of-1 trial compared to those who were treated according to usual care.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation